2016
DOI: 10.1186/s12909-016-0533-4
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and assessment of personal and professional development skills in a pharmacy curriculum

Abstract: BackgroundHealth sciences programs are increasingly expanding their curricula to bridge foundational scientific knowledge with needed skills to practice and patient care. The primary objectives of this study are to 1) assess whether the personal and professional development (PPD) subdomains (self-assessment, leadership, innovation and entrepreneurship, and professionalism) are integrated in a pharmacy curriculum; and 2) identify any gaps related to the subdomains’ learning objectives.MethodsFour different mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 22 publications
0
49
0
Order By: Relevance
“…Pharmacy schools have implemented multiple mechanisms to promote the personal and professional growth of all students, including specialized courses and co-curricular activities to develop leadership, problem solving, and professionalism. 12,13,14,19 In addition, many programs have introduced pharmacy students to the use of selfassessment tools such as Myers Brigg, Strength Finders, emotional intelligence, grit, and the Birkman Method. 20,21,22,23,24 Addition of the IDP facilitates tracking of each individual student and aids in ensuring that the available programmatic offerings to promote personal and professional development are being synthesized and applied as intended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacy schools have implemented multiple mechanisms to promote the personal and professional growth of all students, including specialized courses and co-curricular activities to develop leadership, problem solving, and professionalism. 12,13,14,19 In addition, many programs have introduced pharmacy students to the use of selfassessment tools such as Myers Brigg, Strength Finders, emotional intelligence, grit, and the Birkman Method. 20,21,22,23,24 Addition of the IDP facilitates tracking of each individual student and aids in ensuring that the available programmatic offerings to promote personal and professional development are being synthesized and applied as intended.…”
Section: Discussionmentioning
confidence: 99%
“…11 Multiple mechanisms have been developed by pharmacy schools to address the key elements of personal and professional development, including specialized coursework, targeted curricular elements and co-curricular activities. 12,13,14 Additionally, validated assessment tools to measure these key elements are still being developed, particularly for pharmacy students. Nevertheless, ensuring the application of these personal and professional development elements are essential, especially as opportunities expand in the pharmacy profession, and many students A J P E A c c e p t e d D r a f t express concerns about being able to navigate their career choices and prepare themselves for these varied roles.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 2007, domestic scholars have made clear comparison and analysis of employability of full-time and in-service doctoral students, suggested that general colleges have certain limitations in cultivation of medical college students' employability, which is also the case for innovation and entrepreneurship education as their employability does not directly correspond to employers' need (Ramia et al, 2016). Innovation and entrepreneurship education and training model should be closely linked with the industry, employment relationship should be clarified by real interest relationship, which is an acting point for innovation and entrepreneurship education to improve medical college students' employability (Singh et al, 2015;Flaherty et al, 2017).…”
Section: Status Of Domestic Researchmentioning
confidence: 99%
“…Many universities have begun to recognize the value of professional development programs in the balance of work/study/life across different disciplines [1,6,7] . The four most relevant professional attributes for engineering PhDs were identified in one study as creativity, good communication skills, multi-disciplinarity, and strong analytical skills [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Universities which have acted on this need have mostly implemented preliminary surveys, supplementary workshops, and online resources [1,6,7,10] . One pilot study was conducted at Purdue University to provide graduate students with a graduate level course called "Preparing Future Professionals" [11,12] .…”
Section: Introductionmentioning
confidence: 99%